Prospective Randomized Double-blinded Trial Comparing 2 Anti-MRSA Agents With Supplemental Coverage of Cefazolin Before Lower Extremity Revascularization. Issue 3 (September 2015) - Stone, Patrick A.; AbuRahma, Ali F.; Campbell, James R.; Hass, Stephen M.; Mousa, Albeir Y.; Nanjundappa, Aravinda; Srivastiva, Mohit; Modak, Asmita; Emmett, Mary
Abstract : Objective: To compare with antibiotics with methicillin-resistant microbial coverage in a prospective fashion. Background: Current antibiotic prophylaxis for vascular procedures includes a first generation cephalosporin. No changes in recommendations have occurred despite changes in reports of incidence of MRSA related surgical site infections. Does supplemental anti-MRSA prophylactic coverage provide a significant reduction in Gram-positive or MRSA infections? Methods: Single center prospective double blinded randomized study of patients undergoing lower extremity vascular procedures from 2011 to 2014. One hundred seventy-eight (178) patients were evaluated at 90 days for surgical site infection. Infections were categorized as early infections less than 30 days of the index procedure and late after 90 days. Results: Early vascular surgical site infection occurred in 7(8.24%) of patients in the Vancomycin arm, and 11 (11.83%) in the Daptomycin arm ( P = 0.43). Gram-positive related infections and MRSA infections occurred in 1(1.18%)/0(0%) of Vancomycin patients and 9 (9.68%)/1 (1.08%) of Daptomycin patients, respectively ( P < 0.02 and P = 1.00). Readmissions related to surgical site infections occurred in 4(4.71%) in the Vancomycin group and 11 (11.8%) in the Daptomycin group ( P = 0.11). Patients undergoing operative exploration occurred in 5 (5.88%) in the Vancomycin group and 10 (10.75%) of the Daptomycin group ( P = 0.17). Late infections were reported in 3 patients, 2 of which were in the combined Daptomycin group. Median hospital charges related to readmissions due to a surgical site infection was $50, 823 in the combination Vancomycin arm and $110, 920 in the combination Daptomycin group; however, no statistical significance was appreciated ( P = 0.11). Conclusions: Vancomycin supplemental prophylaxis seems to reduce the incidence of Gram-positive infection compared with adding supplemental Daptomycin prophylaxis. The Incidence of MRSA-related surgical site infections is low with the addition of either anti-MRSA agents compared with historical incidence of MRSA-related infection. Abstract : Lower extremity surgical site infections after vascular procedures currently isolate methicillin resistance staphyloccous (MRSA) most frequently. We prospective evaluated 2 anti-MRSA agents supplementing cefazolin in 178 patients. Gram-positive infections were reduced when vancomycin administered compared with daptomycin but not MRSA infections 1(1.18%)/0(0%) and 9(9.68%)/1(1.08%), respectively ( P < 0.02 and P = 1.00).